1998
DOI: 10.1128/aem.64.8.3099-3101.1998
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of C 18 -Carboxypropylbetaine and Glass Bead DNA Extraction Methods for Detection of Mycobacterium bovis in Bovine Milk Samples and Analysis of Samples by PCR

Abstract: The purpose of this prospective study was to compare two different milk preparation methods to assay for the presence ofMycobacterium bovis by PCR. Detection by a C18-carboxypropylbetaine (CB-18)-based sample processing method was compared to extraction of DNA from milk with glass beads. Samples from 17 skin test-positive cattle were analyzed. Following CB-18 processing and glass bead extraction, the sensitivity of IS6110-based PCR was 94.1 and 58.8%, respectively (P < 0.025). Because CB-18 processing will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 6 publications
1
20
0
1
Order By: Relevance
“…Importantly, a high number of animals present M. bovis in their noses, as demonstrated by PCR and culture. As it has already been observed with culture and PCR of M. bovis in bovine milk (Cornejo et al, 1998;Zumárraga et al, 2005), PCR is more sensitive than culture, a fact that may be attributable to the decontamination method before culture that may kill a high proportion of bacteria.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Importantly, a high number of animals present M. bovis in their noses, as demonstrated by PCR and culture. As it has already been observed with culture and PCR of M. bovis in bovine milk (Cornejo et al, 1998;Zumárraga et al, 2005), PCR is more sensitive than culture, a fact that may be attributable to the decontamination method before culture that may kill a high proportion of bacteria.…”
Section: Discussionmentioning
confidence: 89%
“…In conclusion, in a herd infected by the same strain, ante-mortem direct and immune-diagnostic parameters change, suggesting that several tests are needed for a faster control of infection at herd level. detect members of the M. tuberculosis complex and is especially useful for the direct detection of M. bovis in bovine tissue samples (Kolk et al, 1992;Kox et al, 1994;Liebana et al, 1995;Wards et al, 1995;Cornejo et al, 1998;Vitale et al, 1998;Zanini et al, 1998Zanini et al, , 2001Romero et al, 1999;Zumárraga et al, 2001Zumárraga et al, , 2005) Eradication of this disease remains an important goal in several countries. The strategy of test and slaughter has been used widely in an attempt to control dissemination of the disease and is based on the tuberculin skin test as a means for BTB diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery of MAP from liquid milk relies on chemical decontamination of the sample to inactivate undesirable micro-organisms that could contaminate agar slopes. Although a range of decontamination procedures have been used (Sweeney et al 1992;Miller et al 1996;Cornejo et al 1998;Rahn et al 1998), Dundee et al (2001 concluded that the decontamination protocol involving 0AE75% (w/v) hexadecylpyridinium chloride (HPC) for 5 h at room temperature was the most sensitive for the recovery of MAP from liquid milk. While a decontamination step may be used to isolate MAP from cheese or other dairy products, such a step has implications for the accurate enumeration of MAP .…”
Section: Introductionmentioning
confidence: 99%
“…paratuberculosis from milk and the method showed promise. The use of CB-18 in decontamination protocols for M. bovis has previously been reported (Cornejo et al 1998;Thornton et al 1998). CB-18 is a zwitterionic detergent and its use during decontamination may increase the recovery of mycobacteria by centrifugation (Anonymous 1998).…”
Section: Discussionmentioning
confidence: 99%
“…There is some uncertainty about whether current pasteurization conditions are capable of inactivating M.a. paratuberculosis if present in raw milk (Chiodini and Hermon-Taylor 1993;Grant et al 1996Grant et al , 1998Hope et al 1997;Stabel et al 1997). As a consequence, there has been recent increased activity towards developing and optimizing methods for the isolation of viable M.a.…”
Section: Introductionmentioning
confidence: 99%